Economic Crises and Returns to University Education in Middle-Income Countries : Stylized Facts and COVID-19 Projections - Fasih, Tazeen; Patrinos, Harry A.; Shafiq, M. Najeeb (World Bank, Washington, DC, 2020)
This paper documents stylized facts on rates of returns to education during economic crises. It shows from three middle-income countries -- Indonesia, Pakistan, and South Africa -- that the rate of return to university education (versus secondary education) has increased during economic crises. Based on this stylized fact, the paper projects that the returns for university graduates may increase by at least one-quarter to one-third during the COVID-19 pandemic.